“Now We All Share the Same Knowledge Base”-Evaluating Professional Development Targeting Preschool Staff’s Understanding of Autism and Inclusion Skills - Petersson-Bloom, Linda; Bölte, Sven (Frontiers in Education, 2022)
Using a mixed-methods intervention approach this study examined the impact and process of a professional development and whether it induces changes in attitudes and practices related to autism among preschool professionals. We assessed professionals’ understanding of autism and their inclusion skills using questionnaires, audio-recorded seminars, and interviews pre-and post-intervention. Professionals, children with autism, and their parents participated. The results indicate that professional development improved attitudes and inclusive practices related to autism as experienced by professionals and parents but not as evident by autistic children. We conclude that professional development is likely to improve preschool staff’s autism knowledge and skills that may be beneficial to create inclusive education and enhance equity and learning outcomes for children with autism. We discuss organizational prerequisites as decisive for the implementation of professional development.